Methodological approaches and principles to the development of polyethnic culture by schoolboys in social-cultural activities (Journal of Educational Sciences, 2017)
The article discusses social-cultural activity as significant means of development of poly-ethnic culture of schoolchildren. The presented approaches and principles, which should ensure the efficiency of the process of development of the multiethnic culture of students. Described systemic activity, ethnic pedagogical, humanistic approaches, and alsothe principles of humanization, cultural conformity, and psychological comfort. It is concluded that the complex following the above-mentioned principles and approaches should ensure the successful development of multi-ethnic culture among schoolchildren at social and cultural activities. Priority socio-cultural activities (including within educational institutions) is to create an enriching environment life personality space “of proximal development”, pedagogical potential which is determined by the morally saturated interpersonal and intercultural communication, a substantial variety of leisure time acting as an effective medium of socialization and the most important means of development of poly-ethnic culture of schoolboys. Systematic methodological approaches-the principles and practical rules as requirements for the organization of the educational process in the school. The logic of the presentation of an article constructed according to the description of the approaches and principles and the development of specific rules for the organization of the educational process in the school.
Keywords: multi-ethnic culture; approaches; principles; social-cultural activities